The effect of commercialization of culture on the Ifugao youth : a case study of two Ifugao municipalities in Northern Luzon, Philippines - Sandvik, Anniken Renslo (Chulalongkorn University, 2013)
Thesis (M.A.)--Chulalongkorn University, 2011